(untitled) (diségno, 2024)
Infinite dialogue “Could it be that the secret of a landscape’s enchantment lies in a certain harmony of forms and light, whose hold over us is as powerful and incomprehensible as that of a fragrance, a gaze, or a tone of voice? Or perhaps it depends on some unknown echo of emotions from primitive humans –those who, here and there, deified the most remarkable objects of nature– springs, rocks, peaks, great trees –and, unknowingly, by isolating them, giving them names, and imparting to them a sort of life, transformed them into true works of art; the most ancient art, that of feeling that an expression arises from an impression, and a particular moment becomes a monument of memory– a sublime gift of a prodigious dawn or sunset, the sacred dread of a forest, the exultation on the heights from which the realms of the earth are revealed? But if we are unable to reason clearly about such emotions, we must nevertheless acknowledge that we are less inept at reproducing them” [read more]